1992
DOI: 10.1002/bip.360320602
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of peptide conformations induced in anisotropic environments

Abstract: Reversed-phase high performance liquid chromatography (RP HPLC) has been found to be a convenient and powerful tool for the study of the secondary structure of peptides. Here, the ability of proline to perturb the secondary structures of peptides induced at aqueous-lipid interfaces and the induced conformation of polyproline peptides were investigated by means of RP HPLC. For these studies, four different complete sets of substitution analogues of model peptides expected to have specific induced conformations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…[34] Although RP-HPLC separates peptides mainly by hydrophobic interactions, the induced peptide secondary structures also influence their retention times. [34] The substitution of Lys for Pro in MEP-1 reduced the hydrophobicity of the peptide in a way that theoretically should shorten its retention time measured on the C-18 RP-HLC column.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Although RP-HPLC separates peptides mainly by hydrophobic interactions, the induced peptide secondary structures also influence their retention times. [34] The substitution of Lys for Pro in MEP-1 reduced the hydrophobicity of the peptide in a way that theoretically should shorten its retention time measured on the C-18 RP-HLC column.…”
Section: Discussionmentioning
confidence: 99%
“…[34] Although RP-HPLC separates peptides mainly by hydrophobic interactions, the induced peptide secondary structures also influence their retention times. [34] The substitution of Lys for Pro in MEP-1 reduced the hydrophobicity of the peptide in a way that theoretically should shorten its retention time measured on the C-18 RP-HLC column. However, as shown in Table 3, this peptide eluted much later than MEP, suggesting, that the bend in the a-helical structure of MEP imposed by Pro somehow perturbs the hydrophobic interactions of the MEP with the C-18 stationary phase, making it more "movable" within the column.…”
Section: Discussionmentioning
confidence: 99%
“…It has in fact been shown that for model peptides, retention times are correlated to both structuring and amphipathicity, and directly correlated to the antimicrobial activity. 184 All the above considerations lead to the conclusion that the ability to structure into a well-defined, amphipathic ␣-helix is strongly correlated to antimicrobial activity. On the other hand, formation of a helical structure before membrane interaction may not be beneficial.…”
Section: Structurementioning
confidence: 99%
“…This is not surprising as Pro is the well-known "helix-breaker" [20][21][22]. In this sequence framework, the prediction error is particularly high when substitution at position (6) is hydrophilic, i.e.…”
Section: Replacement Of the "Helix-breaker" Pro(6)mentioning
confidence: 87%